Silence, Absence, and Forgetting: Traditional Music and Dance Contests of Gaelic Cape Breton - Sparling, Heather (MUSICultures, 2023)
A documented history of cultural competitions and contests in Gaelic Cape Breton is being deliberately forgotten. Drawing on Paul Connerton’s theory of social forgetting, the author suggests that this has happened for ideological reasons involving the construction of Gaelic culture as participatory and inclusive, characteristics that many Cape Bretoners find irreconcilable with competitions. By examining historical evidence demonstrating that cultural contests and competitions existed in Cape Breton at various times and in various places, and how they relate to a broader, international context of competitions in “Celtic” cultural communities, the author concludes that present-day claims about the absence and insignificance of contests are inconsistent with the historical record.